Leading markers of risk culture in organization - Gorzen-Mitka, Iwona (European Journal of Sustainable Development, 2018)
Among the many assumptions about taking-risk widely embraced but rarely tested is the notion that large companies risk culture are less averse to risk than risk culture in the SMEs sector. Taking a multivariate markers of organizational culture, this study seeks to identify and to explain differences between theoretical and empirical aspects of risk culture. The concept of risk culture pertains to perceptions risks and promote risk-taking in organizations. I accept the assumption that organizational culture markers (indicated mainly based on research and opinion large companies) depends on the company size. Using questionnaire data from a variety of SMEs organizations, I find that there is considerable variance in theoretical and practical risk culture markers. I postulate that culture influences corporate risk-taking according organizational size. The primary purpose of this research is to contribute to the understanding of the risk culture markers in micro small and medium size enterprises. The research questions explore the differentiation between risk culture markers indicates in academic literature and markers indicates in empirical research. Theoretical considerations is supplemented by a results of the study in 269 Polish SMEs. Additional aim of this study is, at least partially, fill a gap on the organizational culture and risk management in SMEs.